Wakelet-Assisted Qawāʿid ʿArabiyyah Learning Based on Prophetic Wisdom: A Case Study at Islamic Boarding Schools in Malang - Dien Nur Chotimah (Lughawiyah: Journal of Arabic Education and Linguistics, 2026)
The mastery of qawaid arabiyah among students often faces challenges in terms of monotonous learning approaches and lack of value instilling. This study aims to explore the use of the wakelet platform in learning qawaid arabiyah based on the value of al-hikmah al-nabawiyah in the al-Khansa' Malang student boarding school and identify the benefits and challenges of using the wakelet as a learning medium in a religious context. This qualitative research uses an intrinsic case study approach. Data were drawn from in-depth interviews, participatory observations, and digital learning documents. Data analysis is carried out by thematic analysis with stages: transcription and verification of data, coding, code grouping, and interpretation and drawing conclusions. The results of the study show that the wakelet digital platform is applied with multi-component integrative learning, including digital media, linguistic materials, prophetic values, pedagogical strategies, and student transformation. The use of this platform not only supports the cognitive aspect, but also the affective and spiritual aspects of students. This study recommends the development of a digital learning model based on prophetic mileage as a strategic alternative to learning Arabic in Islamic boarding schools. These findings have implications for the design of integrative curriculum based on technology and spiritual values.